Structuring GUI Acceptance Tests based on Usage Scenarios - Liebel, Grischa (My University, 2013)
Software testing plays an important role in the overall software development process. However, many areas of software testing are still unexplored, or contain gaps in their existing body of knowledge, such as the area of GUI acceptance and system testing. This thesis aims to bridge this gap with results from a multiple-case study with the goal of investigating the current state of GUI acceptance and system testing in industry. The study was performed with six software development companies, of different size and context, to acquire broad information and a general overview of industrial state-of-practice. From the acquired information, the PASTA framework on how to approach GUI acceptance and system testing has been derived. The framework contains guidelines for two approaches to GUI acceptance and system testing. Firstly, an organised-level testing approach and secondly a base-level testing approach. Furthermore, these guidelines represent a holistic approach to this type of testing, with practices for test suite design, test scenario elicitation, test automation, and test maintenance. Finally, the thesis presents how these practices were evaluated with the participating companies. Results of the thesis show that the framework can increase the benefits of GUI acceptance and system testing. Consequently, the results of this work help to bridge the current gap in knowledge and constitute a valuable contribution to industry.
Keywords: Data- och informationsvetenskap; Computer and Information Science